(untitled) (Slavic Studies, 2024)
Phraseology is a reflection of mentality, culture, social development and the way speakers perceive the world. Somatisms, as phraseological units that contain a reference to at least one part of the body, have a particularly important place in phraseology. This article is an attempt to analyse the somatism “Heart” in Macedonian and German, in order to determine the similarities and differences between the two languages. This is achieved by using and supplementing the metaphorical concepts of Lakoff and Johnson (2004) that extend the concept of the metaphor beyond the classical rhetorical definitions and indicate that metaphorical expressions usually suggest cognitive patterns known as metaphorical concepts, that express different emotions such as love, fear, joy, sadness etc.